SOCIAL-CULTURAL VALUE AND DEVELOPMENT CONSTRAINS MOA BUFFALO FARMING IN MALUKU PROVINCE - Tatipikalawan, Jomima M; Sangadji, Insun (Fakultas Pertanian, Universitas Janabadra, 2023)
This study analyzes the factors that influence the socio-cultural value of the Moa buffalo and identifies the development constraints and solutions to overcome these constraints. The purposive sampling method was used to choose 261 buffalo farmer respondents in Maluku Province, Indonesia. Data were analyzed descriptively and by using multiple linear regressions. The results showed that the socio-cultural value of the Moa buffalo was included in the medium category, which means that the Moa buffalo has socio-cultural values and can be developed. The socio-cultural function of the Moa buffalo was strongly influenced by age, education period, motives for raising buffalo, and the number of buffalo ownership (p<0.01). The number of family members was not statistically significant. All factors together influence the socio-cultural function of the Moa buffalo (R2=0.684). The constraints to the Moa buffalo development are the traditional maintenance system and simple technology, limited feed and water, low access to information and communication, minimal visiting of extension agents, and not being programmed.Keywords: Buffalo Moa, social cultural values, development constrains